2012
DOI: 10.4014/jmb.1108.08087
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Diversity of Carbofuran-Degrading Bacteria Isolated from Agricultural Soils

Abstract: Thirty-seven carbofuran-degrading bacteria were isolated from agricultural soils, and their genetic and phenotypic characteristics were investigated. The isolates were able to utilize carbofuran as a sole source of carbon and energy. Analysis of the 16S rRNA gene sequence indicated that the isolates were related to members of the genera Rhodococcus, Sphingomonas, and Sphingobium, including new types of carbofuran-degrading bacteria, Bosea and Microbacterium. Among the 37 isolates, 15 different chromosomal DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Therefore, our findings are in agreement with several publications that report that microorganism consortium is capable of transforming the environment where they are placed and/or found (Binks et al, 1996;Kanaly et al, 2000;Carvalho et al, 2002;Haruta et al, 2002;Li and Gu, 2007;Itah et al, 2009;Khalid et al, 2009;Kim et al, 2009;Fang et al, 2010;Hua et al, 2010;Radwan et al, 2010;Rajasekar et al, 2010;Jandandhu and Fulekar, 2011;Sakultantimetha et al, 2011;Waranusantigul et al, 2011;Chanthamalee and Luepromchai, 2012;Juárez-Ramirez et al, 2012;Turgay et al, 2012;Shin et al, 2012;Simarro et al, 2013).…”
Section: Molecular Identificationsupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, our findings are in agreement with several publications that report that microorganism consortium is capable of transforming the environment where they are placed and/or found (Binks et al, 1996;Kanaly et al, 2000;Carvalho et al, 2002;Haruta et al, 2002;Li and Gu, 2007;Itah et al, 2009;Khalid et al, 2009;Kim et al, 2009;Fang et al, 2010;Hua et al, 2010;Radwan et al, 2010;Rajasekar et al, 2010;Jandandhu and Fulekar, 2011;Sakultantimetha et al, 2011;Waranusantigul et al, 2011;Chanthamalee and Luepromchai, 2012;Juárez-Ramirez et al, 2012;Turgay et al, 2012;Shin et al, 2012;Simarro et al, 2013).…”
Section: Molecular Identificationsupporting
confidence: 82%
“…They concluded that the rhizosphere bacteria have the potential to improve the efficiency of phytoremediation of plumb and nickel-contaminated sites. Shin et al (2012) have isolated thirtyseven carbofuran-degrading bacteria through enrichment processes from a variety of rice paddy soils and among them they found a species of Microbacterium (M. oxydans) that was able to degrade this pesticide. Microbacterium was isolated from a biofilm capable of degrading 4-aminonaphthalene-1-sulfonic acid used in the process of decolorization of azo dyes (Juárez-Ramirez et al, 2012).…”
Section: Molecular Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several polluted environments have been chosen as target sites for searching genes for organic-compounds degradation (Choi et al, 2009;Herrick et al, 1997;Zhang and Anderson, 2012), antibiotic resistance (Smalla et al, 2000) and heavy-metal resistance (Rajkumar et al, 2012;Smit et al, 1998) among others, and many of those loci have been demonstrated to be encoded on plasmids and other mobile genetic elements (MGE) (Anjum et al, 2012;Sharma and Thakur, 2009;Shin et al, 2012;Tabata et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria of the genus Bosea , which occurred at high densities in our leafhopper samples, have been linked to nitrogen metabolism (denitrification in soil) and occur in the hind wall of the cockchafer gut (Alonso‐Pernas et al, ; Dandie et al, ). Bosea have also been associated with detoxification of bendiocarb and carbofuran insecticides (Jiménez‐Arévalo, Ahuatzi‐Chacón, Galíndez‐Mayer, Juárez‐Ramírez, & Ruiz‐Ordaz, ; Shin, Kim, Seong, Song, & Ka, ). Sandaracinus bacteria have been associated with the degradation of complex molecules including starch (Mohr, Garcia, Gerth, Irschik, & Müller, ; Sharma, Khatri, & Subramanian, ) and in sterol synthesis (Wei, Yin, & Welander, ).…”
Section: Discussionmentioning
confidence: 99%